2005
DOI: 10.5271/sjweh.843
|View full text |Cite
|
Sign up to set email alerts
|

Different mechanisms to explain the reversed effects of mental health on work characteristics

Abstract: Objectives The number of longitudinal studies reporting evidence for reversed effects of strain on work is growing, but evidence regarding the mechanisms underlying such effects is scarce. In this study, earlier longitudinal findings were reviewed, and the following four mechanisms for reversed effects were proposed that reflect within-person or environmental changes: (i) the rosy perception mechanism, (ii) the gloomy perception mechanism, (iii) the upward selection mechanism, and (iv) the drift mechanism.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
162
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(181 citation statements)
references
References 47 publications
15
162
1
1
Order By: Relevance
“…Sample size ranged from 52-2255, and study duration ranged from 3 months to as long as 11 years. Sixteen studies featured two measurement waves (50-56, 58-63, 65, 68, 70), four featured three waves (57,66,67,69), two featured four waves (22,64), and one study featured six measurement waves (29). Of note, eight studies explicitly indicated that job changers (over the course of the study) were excluded from analysis (52,56,57,59,64,65,67,70).…”
Section: Methodological Properties Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Sample size ranged from 52-2255, and study duration ranged from 3 months to as long as 11 years. Sixteen studies featured two measurement waves (50-56, 58-63, 65, 68, 70), four featured three waves (57,66,67,69), two featured four waves (22,64), and one study featured six measurement waves (29). Of note, eight studies explicitly indicated that job changers (over the course of the study) were excluded from analysis (52,56,57,59,64,65,67,70).…”
Section: Methodological Properties Of Studiesmentioning
confidence: 99%
“…During the appraisal process, it was recognized that two pairs of studies analyzed data drawn from the same dataset. This involved two studies by de Lange et al (22,64) and two studies by Houkes et al (61,62). To avoid double-counting, it was determined that only one of each pair of studies should be counted.…”
Section: Synthesis Of Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…Bullying has been defined as an escalating process (e.g., Zapf, & Gross, 2001) and for a complete understanding of this phenomenon it is important to consider its short-term consequences. Moreover, it has been argued that the selection of the temporal lag between measurements should correspond with the "causal interval" of the process under study (Kenny, 1975;De Lange, 2005;Taris & Kompier, 2003). In this sense, as workplace bullying has been defined as a situation where an employee is exposed to repeated and enduring negative acts on at least a weekly basis for a period of minimum 6 months (Einarsen et al, 2003;Leymann, 1996).…”
mentioning
confidence: 99%